Soil quality in mango producing areas in Magdalena State, Colombia (Bioagro, 2023)
Sugar mango (Mangifera indica L.) is cultivated in the department of Magdalena, municipalities of Santa Marta and Cienaga mainly, where it expresses its best agronomic behavior and best fruit quality. Its high demand has generated the need to increase the cultivation areas; however, there are no defined criteria to identify potential areas for its establishment. The study consisted of constructing a soil quality index for sugar mango production, based on twelve physical and fifteen chemical indicators of the soil. In six sugar mango farms in the department of Magdalena, three plots per farm of 350 m2 were selected and the properties of the soils were characterized in each plot. The characteristics of the soil where the cultivar expresses its highest yield and fruit quality were the reference indicators. The soil quality indicator was formulated based on the variables that explained greater variability and were more redundant based on their correlations. Additionally, a weight was given to each variable depending on its importance for agronomic behavior of the cultivar. The soil indicators showed variation, especially the nutrients Zn, Cu, Fe, S, and P in the chemical properties and infiltration and structure index in the physical properties. The chemical and physical variables with the greatest weight were pH and sand content, respectively. The proposed soil quality index turned out to be a good method to classify soil quality for sugar mango production based on physical and chemical soil indicators.
Keywords: Indicators; productivity; soil fertility; soil properties